Pelaksanaan Eksekusi Pengosongan Lahan Yang Telah Berkekuatan Hukum Tetap Di Wilayah Hukum Pengadilan Negeri Bangkinang - Syahrial, Syahrial; Intan Pratiwi, Maya; Saputra, Rian Prayudi (PT PUSTAKA CENDEKIA GROUP, 2023)
Execution is a matter of carrying out a court decision which has permanent legal force. The court verdict that is being executed is the one that has substance order to one of the parties to pay some money or in other case the implementation of the judge’s decision that has ordered to empty fixed object, while the losing party does not want to implement the decision voluntarily so that it requires coercive effort from the court to implement the following matter. Therefore, the land clearing execution in accordande to the civil court decisions that have permanent legal force at Bangkinang District Court is the real execution as well as an execution of some money payment in accordance with the applicable provision. The obstacles within the execution of land clearing of civil case decisions that have permanent legal force at the Bangkinang District are various such as the executed wealth does not exist, the decision’s trait is declarator, the object of execution in the hands of third-parties, execution of the tenants, the object being executed were guaranteed to the third-parties, the land to be executed has no clear boundary, the change in the status of land to state land, the object of execution is abroad, two decisions are different from each other, and for the last, the execution of shared assets. The efforts made in the execution of land clearing of civil case decisions that have permanent legal force at the Bangkinang District Court are ordinary legal efforts divided into resistance (verzet), appeals, and also cassation while the special legal remedies are divided into judicial review (civil request) and the resistance from a third party (derdenverzet).